The presence of diatom frustules in selected river and sea waters in Johor - Chai, Chean Nee (2014)
Diatoms could be found in person whose death was caused by drowning whereby substantial amount of water was consumed into his body. In such instance, diatoms would usually be found in lungs as well as other internal organs. Presence of silica-cell wall makes diatoms resistant to enzymatic and acid digestion in human body, thereby of benefit to post-mortem analysis. Diatoms could be associated to dead body and to location of the drowning incident which assist in determining the cause of death. Hence, diatom is valuable in forensic research. The present study is a preliminary work to explore the morphologies of diatoms which is useful for forensic investigation. In this study, water samples from selected rivers and seas in the state of Johor, Malaysia were collected, preserved and kept under 4°C. Acid digestion method was carried out to extract diatom cells and viewed under light microscope. The presence of diatom cells from both fresh and sea water were detected at the magnification of 400x and 1000x. Diatom frustules were observed and morphologies of these diatoms were examined. It was found that the diatoms of Nitzschia and Navicula were observed in most of the study regions. From their distinctive frustules appearances found in the water resources from Johor Bahru, Mersing and Pontian, the suggested diatom genera also included Melosira, Skeletonema, Coscinodiscus, Thalassiosira, Gyrosigma, Cocconeis. There were also several unidentified diatoms present that would need further studies. The present study has introduced a good exposure to diatom morphologies from selected water resources in supporting the use of diatoms in forensic aspect.